Nuclear energy in the global energy landscape: advancing sustainability and ensuring energy security? - Bassam Fattouh; Sara Vakhshouri (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2024)
Following the Russia-Ukraine war, the issue of energy security has once again surged to the forefront of global discussions. The disruption and threats to global energy security caused by the war have starkly exposed the vulnerability of energy supply chains, accentuating the pressing need for robust and secure energy sources. In this context, different countries, notably in the European Union, have emphasized the pivotal role of nuclear power generation in addressing these concerns and ensuring energy security. The recently signed global stocktake agreement at COP28 also emphasizes the significance of nuclear energy in the broader context of the energy transition and the acceleration of zero- and low-emission technologies. As we find ourselves at the vanguard of an unprecedented energy transition towards sustainable, low-carbon, and environmentally responsible energy supplies, nuclear power emerges as a compelling solution to the energy trilemma. Nevertheless, expanding the role of nuclear energy is far from straightforward, characterized by intricate challenges spanning economic viability, cost-effectiveness, fuel supply dynamics, evolving technologies, regulatory frameworks, public acceptance, and the intricate geopolitics intertwined with the expanding role of nuclear energy. This issue of the Oxford Energy Forum explores nuclear energy's multifaceted role along four key themes: – 1. The cases for and against nuclear power: The initial section presents articles that provide compelling arguments both for and against nuclear power generation, facilitating a balanced discourse on its merits and limitations. – 2. Technological advancements in nuclear energy: This section delves into the latest technological advancements in the field of nuclear energy including SMRs and nuclear fusion, shedding light on innovations poised to enhance safety and efficiency. – 3. Country and regional experiences: The third section casts a discerning eye on the geographical expansion of nuclear energy, examining its adoption across various regions and the unique challenges and opportunities presented by this global diversification. – 4. Geopolitics of nuclear energy and medical isotopes: The final section delves into the geopolitics of nuclear energy and recognizes the interconnectedness between the growth of the nuclear industry and the geopolitics of nuclear medical isotopes.
Keywords: 330